2010
DOI: 10.1038/ki.2009.519
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of metabolic acidosis in patients with low GFR reduced kidney endothelin production and kidney injury, and better preserved GFR

Abstract: Metabolic acidosis often accompanies low glomerular filtration rate and induces secretion of endothelin, which in turn might mediate kidney injury. Here we tested whether treatment of metabolic acidosis in patients with low glomerular filtration rate reduced the progression of kidney disease. Fifty-nine patients with hypertensive nephropathy and metabolic acidosis had their blood pressure reduced with regimens that included angiotensin-converting enzyme inhibition. Thirty patients were then prescribed sodium c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
255
2
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(271 citation statements)
references
References 40 publications
9
255
2
5
Order By: Relevance
“…Indeed, metabolic acidosis in CKD is associated with more rapid CKD progression [30,31] and increased mortality [32] . Consistently maintaining normal ranges of serum HCO 3 -and correcting acidosis have been associated with favorable clinical outcomes [33][34][35][36][37][38] . Taken together, in early stages of CKD, serum total CO 2 can be normal at the cost of active compensation by individual nephrons.…”
Section: Positive Acid Balancementioning
confidence: 99%
“…Indeed, metabolic acidosis in CKD is associated with more rapid CKD progression [30,31] and increased mortality [32] . Consistently maintaining normal ranges of serum HCO 3 -and correcting acidosis have been associated with favorable clinical outcomes [33][34][35][36][37][38] . Taken together, in early stages of CKD, serum total CO 2 can be normal at the cost of active compensation by individual nephrons.…”
Section: Positive Acid Balancementioning
confidence: 99%
“…Recently, alkali supplementation has been reported to attenuate the deterioration of kidney function in CKD patients with metabolic acidosis. 13,14 These data suggest a pathogenic role of an acidic environment for CKD progression, as well as the potential of therapeutic intervention targeting luminal acidity for CKD treatment. However, there has been only limited information as to how the physiologic low pH level may contribute to, or exacerbate, ROS accumulation in proteinuric kidney disease.…”
mentioning
confidence: 99%
“…Multiple other mechanisms, including those involving angiotensin II and aldosterone, are probably involved as well (6). Wesson et al have shown that endothelin levels are increased (7,8). Other studies have suggested that tubule fluid pH may be an important factor in promoting tubule injury in the presence of proteinuria, with alkalinization, at least in vitro, ameliorating tubule cell injury (9).…”
mentioning
confidence: 99%
“…From a clinical treatment perspective, at this point several studies in the last few years have suggested that the administration of sodium bicarbonate (or other alkali sources, such as citrate or fruits and vegetables) in patients with CKD, even with minimally decreased or even normal serum bicarbonate concentrations, may slow progression (8,(12)(13)(14)(15). Although all of these studies have been relatively small, they all point to a beneficial effect of alkali administration on progression of CKD.…”
mentioning
confidence: 99%
See 1 more Smart Citation